The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/met9111212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ca Content on the Mechanical Properties and Corrosion Behaviors of Extruded Mg–7Li–3Al Alloys

Abstract: The effect of Ca addition on the microstructure, mechanical properties, and corrosion behaviors of the extruded Mg–7Li–3Al alloys was investigated. The results showed that the extruded Mg–7Li–3Al–xCa alloys consisted of α-Mg (hcp) + β-Li (bcc) matrix phases and Al2Ca. With increasing Ca content, the amount and morphology of the Al2Ca phase changed significantly. The grains of the extruded Mg–7Li–3Al–xCa alloys were refined by dynamic recrystallization during the extrusion process. The tensile tests results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Figure 10 showed various Mg alloys' EL and corrosion rate (in NaCl solutions). [64][65][66][67][68][69][70][71][72][73][74] Although the Mg-Gd-Zn alloys prepared by Srinivasan et al 72 showed a relative fast corrosion rate about 30 mm•y −1 , the EL was not acceptable. In contrast, in spite of better EL shown in Mg-Li-Al(-Ca) alloys (bigger than 15%), 74 the corrosion rates were relatively slower.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 10 showed various Mg alloys' EL and corrosion rate (in NaCl solutions). [64][65][66][67][68][69][70][71][72][73][74] Although the Mg-Gd-Zn alloys prepared by Srinivasan et al 72 showed a relative fast corrosion rate about 30 mm•y −1 , the EL was not acceptable. In contrast, in spite of better EL shown in Mg-Li-Al(-Ca) alloys (bigger than 15%), 74 the corrosion rates were relatively slower.…”
Section: Discussionmentioning
confidence: 99%
“…[64][65][66][67][68][69][70][71][72][73][74] Although the Mg-Gd-Zn alloys prepared by Srinivasan et al 72 showed a relative fast corrosion rate about 30 mm•y −1 , the EL was not acceptable. In contrast, in spite of better EL shown in Mg-Li-Al(-Ca) alloys (bigger than 15%), 74 the corrosion rates were relatively slower. To our best knowledge, only very few researches managed to obtain Mg alloys with both high degradation rate and plasticity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a solid solution its percentage can reach up to 1.34 wt.% according to the binary phase diagrams of Mg-Ca [28,50]. It has been reported that the addition of Ca in Mg alloys improves their mechanical properties and diminishes their corrosion activity [51,52]. Mg-Ca alloys, as a class of novel biodegradable magnesium alloys, have been recommended in the context of medical implants [53], with the advantage of a density like that of human bone [2,54].…”
Section: Introductionmentioning
confidence: 99%